Productive performance and meat quality of commercial Cobb chicken fed diets containing different levels of prickly pear fruits (Opuntia ficus indica) peel - Badr, Sherif E. A. (2021)
Obtained results illustrated that feed intake, live body weight, feed conversion ratio of broiler fed diet containing PPP were better (P < 0.05) than that of control. Broilers fed diet containing 5, 10, and 15% PPP were heavier (P < 0.05) by 1.60, 3.68, and 5.78%, respectively, over those fed the control diet. Inoculation of diets containing PPP achieved high (P < 0.05) carcasses weight and dressing% compared with control. Significant differences (P < 0.05) were detected for serum total protein, and total globulin of blood serum broiler as feeding inclusion levels of tested diets. Broiler fed diets contained 15% achieved higher degrees of taste, color, odor (aroma), texture, and overall acceptability. Highest (P < 0.05) biological value, true-digestibility and net protein utilization of broiler meat-fed PPP than other groups of control which was expected, as casein is a protein source with optimal digestibility.